Weak PS-rings over Skew Hurwitz Series (European Journal of Pure and Applied Mathematics, 2018)
The notion of PS-rings is extended to the class of weak PS-rings. Weexplore the algebraic properties of such class and study its relation withmany other rings such as local ring and semisimple NI-ring. Also, weshow the following result concerned, the ring of skew Hurwitz series.Â If R is aweak right PS-ring, then the ring of skew Hurwitz seriesÂ is a weak right PS-ring.
Keywords: PS-modules; PS-rings; skew Hurwitz series rings